Brucella ovis REO 198 natural and experimental infection in Santa Inês rams from Brazil - Nozaki, Cristiane Nakada [UNESP]; Azevedo, Hymerson Costa; De Lira, Nair Silva Cavalcanti [UNESP]; Rodello, Leandro [UNESP]; Filho, Otávio Augusto [UNESP]; Dasso, Maurício Gauterio; Bicudo, Sony Dimas [UNESP]; De Paula Antunes, João Marcelo Azevedo [UNESP]; Megid, Jane [UNESP] (Universidade Estadual de Londrina, 2013)
B. ovis pathogenicity was evaluated in experimentally inoculated and naturally infected rams. Ten animals were submitted to simultaneous conjunctival and intrapreputial inoculation with 2x109 CFU/ mL of B. ovis REO 198. After that, animals underwent physical examination and blood samples were collected for serology every week. Positive serology results started to be observed in the 3rd week, with fluctuations in titers. Clinical changes began in the 5th week after inoculation and were associated with positive serology in the acute phase of the disease. Presence of B. ovis in semen and urine culture was intermittent. Three non-inoculated animals showed natural infection. B. ovis was shed twice in semen of one serology-negative animal. The study underscored the pathogenic characteristics of B. ovis REO 198 in Santa Inês rams, as well as the importance of animals as potential sources of infection.
Keywords: B. Ovis; Brucellosis; Clinical signs; Experimental inoculation; Ovine